Comic Strips Toward Students’ Reading Comprehension Achievement - Ida Yuliani (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2019)
This study focuses on the investigation of the influence of teacher’s teaching technique on student’s reading comprehension achievement using comic strips media. In this study, the writer used a quasi-experimental design. The population of this study is tenth-grade students of SMAN 1 Buay Madang Timurwith 122 students, meanwhile, the writer used purposive sampling as a method for taking a sample. Therefore, class X.MIA 2 was chosen as an experimental group that is taught reading comprehension using comic strips and class X.IIS 2 as a control group who were taught reading comprehension using conventional media. Moreover, the writer used multiple-choice descriptive text. Based on the finding, the mean score of the pre-test experimental group was 50.97 and the mean score of the post-test experimental group was 78.84. While the mean score of the pre-test control group was 38.40 and the post-test score was 43.07 and the result of analyzing the data using SPSS 16, P output was 0.000, It is less than the critical value significance level (0.05). It means that alternative hypotheses (Ha) is accepted and null hypotheses (Ho) is rejected. It can be concluded that there is any significance between the students who are taught by using comic strips media and the students who are taught by using conventional media.